Dose and Time-Dependent Lipopolysaccharide Exposure on A549 Cell Model Influences Pro-Inflammatory Cytokine Interleukin 8 - Sarah Sumayyah; Prayoga Suryadarma; Rachmawati Noverina; Wireni Ayuningtyas; Firman Fuad Wirakusumah; Ahmad Faried (Majalah Kedokteran Bandung, 2023)
Hyperinflammation in COVID-19 patients is one of the causes of the high mortality rate of COVID-19. An in vitro model mimicking the inflammatory responses in COVID-19 patients is important in the efforts of finding new drug candidates for this disease. Lipopolysaccharide (LPS) can increase the proinflammatory cytokine interleukin 8 in response to the presence of foreign substances. This preliminary study sought to explore the use of  the A549 cells as an in vitro inflammatory model. This study was conducted from August to November 2022 at the stem cell research and development laboratory of Bio Farma Indonesia. The exposure of 100, 500, and 1000 g/mL doses of LPS administered for 24, 72, and 120 hours on the A549 cells was analyzed for cell viability, population doubling time (PDT), and the presence of  proinflammatory cytokine IL-8. The group differences were examined using one- and two-way analysis of variance in IBM SPSS Statistics Version 29, with a p-value of 0.05 considered significant. Cells exposed to a dose of 1000 g/mL LPS had a lower viability and a higher proliferation rate (p<0.05) based on the viability and PDT. Viability, PDT, and pro-inflammatory cytokines showed concentration- and time-dependent responses. Therefore, increased levels of the proinflammatory cytokine IL-8 in cells exposed to LPS at a dose of 1000 g/mL for 24 hours can be used as a mimic to study hyperinflammation in COVID-19 patients.